2003
DOI: 10.1111/j.1651-2227.2003.tb02483.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring self‐reported, health‐related, quality of life in adolescents with type 1 diabetes using both generic and disease‐specific instruments

Abstract: Aims: To describe perceived functional health and well‐being and diabetes‐related impact, worry and satisfaction with life in relation to demographic and clinical variables in a population of adolescents with type 1 diabetes. To compare perceived functional health and well‐being between adolescents with diabetes and a group of healthy controls and to analyse the relationship between generic functional health and well‐being and diabetes‐related impact, worry and satisfaction with life. Methods: A total of 130 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
67
4
14

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 24 publications
14
67
4
14
Order By: Relevance
“…When we compared the youths' HRQoL by gender, we found that boys had better perception of quality of life than girls. This gender difference was confirmed in Graue and Kalyva' researches (9,14). We did not find significant relationship between the HRQoL and the metabolic control.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…When we compared the youths' HRQoL by gender, we found that boys had better perception of quality of life than girls. This gender difference was confirmed in Graue and Kalyva' researches (9,14). We did not find significant relationship between the HRQoL and the metabolic control.…”
Section: Discussionsupporting
confidence: 66%
“…We observed controversial results regarding the HRQoL and metabolic control in the literature. Some studies found positive correlation between better HRQoL and good glycemic control (12,14,28), others had no evidence about it (7,9,17). Physical activity is essential to health in people of all ages, but for children plays a key role for their physical and mental health.…”
mentioning
confidence: 99%
“…Nonetheless, associations among QoL and the variables examined in our study were similar to those observed in studies of younger patients. In particular, they showed lower QoL in girls than boys and in older adolescents, and higher QoL in patients using insulin pumps (20)(21)(22)(23)(24). A recent study compared QoL through the KINDL-R questionnaire in diabetic people aged 11-17 with onset of disease at age 4 and lower and in a large control group of non diabetic people, providing evidence of similar scores of QoL in both groups (7).…”
Section: Discussionmentioning
confidence: 99%
“…Świadomość ograniczeń i ewentualnych skutków w przyszłości dotyczy głównie dalszego kształcenia, wyboru zawodu, podejmowania zadań i ról związanych z wiekiem. Młodzież z cukrzycą ocenia swoje ogólne zdrowie podobnie jak zdrowi rówieśnicy (dobrze kontrolowana cukrzyca wiąże się z dobrą adaptacją), ale wiele poszczególnych objawów choroby współwy-stępuje z gorszym fizycznym i psychospołecznym funkcjonowaniem [28].…”
Section: Zagadnienie Wybranych Przewlekłych Zaburzeń Endokrynnychunclassified
“…Brak istotnych różnic w zakresie subiektywnej jakości życia z uwagi na płeć jest wynikiem interesującym, zwłaszcza gdy rezultaty niektórych badań wskazują, że dziewczęta uzyskują niższe wyniki w porównaniu z chłopcami [28]. Międzygrupowe analizy porównawcze dowodzą, że młodzież z cukrzycą cechuje wyższy poziom subiektywnej jakości życia, zwłaszcza w porównaniu do badanych z otyłością.…”
unclassified